2008
DOI: 10.1021/np8001628
|View full text |Cite
|
Sign up to set email alerts
|

Spheciosterol Sulfates, PKCζ Inhibitors from a Philippine Sponge Spheciospongia sp.

Abstract: Three new sterol sulfates, spheciosterol sulfates A−C (1−3), and the known sterol sulfate topsentiasterol sulfate E (4) have been isolated from the sponge Spheciospongia sp., collected in the Philippines. Structures were assigned on the basis of extensive 1D and 2D NMR studies as well as analysis by HRESIMS. Compounds 1−4 inhibited PKCζ with IC50 values of 1.59, 0.53, 0.11, and 1.21 μM, respectively. In a cell-based assay, 1−4 also inhibited NF-κB activation with EC50 values of 12−64 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…The spheciosterol sulfates A-C, isolated from a Spheciospongia sp., were recently shown to inhibit PKCζ and NF-κB activation 6. It was shown that the sterol side chain factors into their PKCζ activity; the longer side chain seen in spheciosterol sulfate C is 5-fold more active than spheciosterol sulfate B, and 10-fold more active than the shorter side chains seen in spheciosterol sulfate A and topsentiasterol sulfate E 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spheciosterol sulfates A-C, isolated from a Spheciospongia sp., were recently shown to inhibit PKCζ and NF-κB activation 6. It was shown that the sterol side chain factors into their PKCζ activity; the longer side chain seen in spheciosterol sulfate C is 5-fold more active than spheciosterol sulfate B, and 10-fold more active than the shorter side chains seen in spheciosterol sulfate A and topsentiasterol sulfate E 6.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the spheciosterol sulfates A–C, isolated from a Spheciospongia sp. sponge, were recently shown to inhibit protein kinase C ζ (PKCζ), as well as downstream NF-κB activation 6. PKCζ has been implicated as an integral factor in several types of cancer,7–11 obesity,12 and osteoarthritis 8,13.…”
Section: Introductionmentioning
confidence: 99%
“…81 However, due to the unclear role of PKC-zeta in VSMC growth, the efficacy of PKC-zeta inhibitor in restenosis is uncertain at present.…”
Section: Pkc Inhibitor and Restenosis Preventionmentioning
confidence: 99%
“…Steroidal compounds as well as phthalate derivatives have been isolated from Spheciospongia sp. (Safaeian et al, 2009;Ma et al, 2004;Whitson et al, 2008). The increasing threat of cancer has initiated a renewal of interest in the search for novel anticancer agents.…”
Section: Introductionmentioning
confidence: 99%